SELECTING SUITABLE FOREST AREAS FOR HONEY PRODUCTION USING THE AHP: A CASE STUDY IN TURKEY - Güngör, Ersin; Sen, G. (FapUNIFESP (SciELO), 2018)
ABSTRACT Honey production forests (HPFs) are crucial forest areas for the preservation and transfer of biodiversity for future generations, provision of sustainable food safety, supporting rural development, and the rehabilitation of barren forests so that society can benefit from them. The purpose of this study is to prepare a model for conducting planning and prioritizing for HPF areas. For this purpose, using a multidimensional decision support model, we determined the most suitable three areas by way of prioritizing potential HPF areas identified. Bartin in Turkey which was chosen as the area of study, in line with the criteria (ecological-environmental, economic, and socio-cultural) set out using the participatory approach. The ranking and analytic hierarchy process (AHP) methods were employed. The results of the study indicate that public institutions and non-governmental organizations (NGOs) prioritize ecological-environmental criteria (especially the type of honey) in their identification of HPFs, whereas the locals care more about the economic criteria, especially the potential for honey production, when identifying HPFs. Moreover, the fact that the level of demand is at the top among the economy-based sub-criteria indicates that the demands and expectations of interest groups should definitely be taken into consideration in the functional provision of forest resources. If HPF areas are planned and established by paying attention to the priorities, HPFs would contribute to an increase in added value and social welfare in the local area as well as to employment, rural development, and the sustainable management of forest resources.
Keywords: Food Safety; Decisions Making; Sustainable forest management; Turkey; Participation; Decisions making; Forestry; Food security; Rural Development; Sustainable Forest Management; Rural development; 2. Zero hunger; 9. Industry and infrastructure; 1. No poverty; 15. Life on land; 12. Responsible consumption; 13. Climate action; 11. Sustainability